Correlations between preweaning traits in Duroc swine - Schlindwein, Antonio Pedro; Duarte, Francisco Alberto de Moura; Spers, Aleksanders; Bezerra, Luiz A. F. (Sociedade Brasileira de Genética, 1982)
Phenotypic, genetic and environmental correlations were determined between litter size and weight and pig weight at birth, 21 and 56 (weaning) days of age for Duroc swine raised at Estação Experimental de Zootecnia, Sertãozinho, SP, between 1957 and 1970. Phenotypic, genetic and environmental variances were determined on the basis of sire variance and covariance components and error adjusted for the effects of year, season and sow age, using the least squares method. The correlation values obtained indicate favorable association between the traits studied, showing that selection for the improvement of one or more traits would also be effective for the improvement of any other. This situation can be better appreciated by examining the correlated response studied in 14 possibilities of indirect selection involving two traits.

Foram determinadas correlações fenotípicas, genéticas e ambientes entre as características tamanho e peso de leitegada e peso dos leitões ao nascimento, 21 e 56 dias (desmama) de idade, em suínos da raça Duroc criados na Estação Experimental de Zootecnia de Sertãozinho, São Paulo, no período de 1957 a 1970. A determinação das variâncias fenotípicas, genéticas e ambientais se baseiam nos componentes de variância e covariância de reprodutor e erro, ajustados para os efeitos de ano, época do ano e idade da porca, utilizando-se o método dos quadrados mínimos. Os valores encontrados para as correlações indicaram associação favorável entre as características estudadas mostrando que a seleção destinada à melhoria de uma ou mais características, seria também efetiva no melhoramento de qualquer outra. Esta situação é melhor avaliada pela apreciação da resposta correlacionada, estudada em 14 possibilidades de seleção indireta, envolvendo duas características.